Gastrointestinal stromal neoplasm in postmenopausal woman: Case report - Llontop, Eddar (2024)
Gastrointestinal stromal tumors (GIST) are the most common mesenchymal tumors that can originate in the digestive tract and are most common in the stomach. Typically accounting for only 0.1% to 3% of gastrointestinal tumors, approximately 10% to 30% are clinically malignant neoplasms. Case presentation: A 66-year-old female patient has a medical history of high blood pressure, cardiac arrhythmia and glaucoma; He was admitted as an emergency and underwent an upper gastrointestinal endoscopy, revealing signs of recent upper gastrointestinal bleeding and a probable pancreatic infiltrating proliferative lesion. 3 days after admission to the emergency room, an abdominal CT scan was performed where a large heterogeneous solid mass was identified. The patient underwent in bloc resection of the mass (pancreas, spleen and gastric portion). Histopathology of the excised specimen was consistent with a high- risk gastrointestinal stromal tumor of the stomach (positive for CD 117). Conclusion: Giant GISTs are rare. Surgical removal with curative intent is feasible; The patient must be studied well to determine resectability.